The line between - Lee, Tosca Moon (Howard Books, 2019)
"In this frighteningly believable thriller from New York Times bestselling author Tosca Lee, an extinct disease re-emerges from the melting Alaskan permafrost to cause madness in its victims. For recent apocalyptic cult escapee Wynter Roth, it's the end she'd always been told was coming"--